Prinsip Muamalah Peraturan Menteri Pertanian Nomor 31/PERMENTAN/OT.140/2/2014 tentang Pedoman Budi Daya Ayam Pedaging dan Ayam Petelur yang Baik - Muhamad Ilham Safari; Zaini Abdul Malik; Liza Dzulhijjah (UNISBA Press, 2024)
Abstract. In Islam, humans are given the freedom to do business as long as the business is in accordance with the principles of muamalah and does not harm others. It is important to pay attention to this so that the business carried out not only generates personal profits, but also provides benefits to many people and the surrounding environment. Kampung Sindang Palay has three chicken farms that are very close to residential areas that are not in accordance with the regulation of the Minister of Agriculture number 31/Permentan/Ot.140/2/2014 The contribution of cage owners who have the potential to provide benefits to the community's economy has a positive impact. Although this problem is often considered trivial, it is very troubling, so its solution requires the truth of the chicken farmers and the support of the local community. Then a qualitative method with an empirical normative approach was used as a research study, with the aim of comparing chicken farming practices with the related Muamalah Principles so that it can be concluded that in practice chicken farming is not carried out in accordance with the Muamalah Principles and Ministerial Regulation no. 31/Permentan/Ot.140/2/2014 which is not fulfilled inestablishing a chicken farm. Abstrak. Dalam Islam, manusia diberikan kebebasan untuk berbisnis selama bisnis tersebut sesuai dengan prinsip-prinsip muamalah dan tidak merugikan orang lain. Penting untuk memperhatikan hal ini agar bisnis yang dilakukan tidak hanya menghasilkan keuntungan pribadi, tetapi juga memberikan manfaat bagi banyak orang dan lingkungan sekitarnya. Kampung Sindang Palay terdapat tiga peternakan ayam yang jaraknya sangat berdekatan dengan pemukiman warga yang belum sesuai dengan peraturan menteri pertenian nomor 31/permentan/Ot.140/2/2014 Kontribusi pemilik kandang yang berpotensi memberikan manfaat bagi perekonomian masyarakat memberikan dampak positif. Meskipun masalah ini sering kali dianggap kecil, namun hal ini sangat meresahkan, sehingga penyelesaiannya memerlukan kebenaran dari para peternak ayam dan dukungan dari daerah setempat. Kemudian digunakanlah metode kualitatif dengan pendekatan normatif empiris sebagai kajian penelitiannya, dengan tujuan membandingkan praktik peternakan ayam dengan Prinsip Muamalah terkait sehingga dapat diambil kesimpulan bahwa dalam Praktiknya peternakan ayam melaksanakan tidak sesuai dengan Prinsip Muamalah dan Permentan no 31/Permentan/Ot.140/2/2014 yang tidak terpenuhinya syarat dalam mendirikan peternakan ayam.